GE_GERICHTE P/3511/2014 vom 27. April 2017 - GE Cour de justice (2017)
DROIT D'ÊTRE ENTENDU ; MOTIVATION DE LA DÉCISION ; NOTIFICATION DE LA DÉCISION ; DOMICILE ; ÉTAT ÉTRANGER ; DOMICILE ÉLU | CEDH.6; Cst.29; CPP.3; CPP.87